Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/ceat.201800271
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Poly(tetrafluoroethylene) Porous Membrane to Superhydrophilicity with Improved Durability

Abstract: The commercial fluorocarbon surfactant (FCS) DuPont Zonyl 321 fluorinated cationic surfactants, was employed to modify both flat-sheet and hollow-fiber poly(tetrafluoroethylene) (PTFE) porous membranes. The variation of morphology, wettability, and hydrophilicity durability to acid and alkali as well as the filtration performance of both membranes were investigated. Such superhydrophilic membranes showed better wetting stability and higher resistance to acid and alkali solutions. Moreover, both membranes exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…First, it has a good acid and alkali resistance functionality compared with ordinary fabrics because of the intrinsic anti‐chemical performance of PTFE sheathed SETY. [ 16 ] As shown in Figure 1a‐i, the ordinary fabrics was corroded and damaged by sulfuric acid, but F‐TENG remained intact. Second, it can be used for self‐powered chemical leakage monitoring (Figure 1a‐ii), as obvious signals can be generated when the chemical droplet slapping on the core‐shell structured hydrophobic yarn.…”
Section: Resultsmentioning
confidence: 99%
“…First, it has a good acid and alkali resistance functionality compared with ordinary fabrics because of the intrinsic anti‐chemical performance of PTFE sheathed SETY. [ 16 ] As shown in Figure 1a‐i, the ordinary fabrics was corroded and damaged by sulfuric acid, but F‐TENG remained intact. Second, it can be used for self‐powered chemical leakage monitoring (Figure 1a‐ii), as obvious signals can be generated when the chemical droplet slapping on the core‐shell structured hydrophobic yarn.…”
Section: Resultsmentioning
confidence: 99%
“…3 indicated that the zeta potential of the pristine PTFE membrane was –8.41 mV. If coated with pure FCS, the zeta potential reversed to 1.05 mV due to the positively charged FCS 38. The zeta potential of the PTFE/FCS‐PEI separator further increased to 5.62 mV due to the coexistence of the positively charged FCS and the PEI.…”
Section: Resultsmentioning
confidence: 99%
“…PEI, which contains abundant polar amine groups, has been regarded as a valid candidate for imparting hydrophilicity and antifouling properties onto membrane surfaces during filtration [41,42]. Herein, PEI could be firmly deposited on the hydrophobic PTFE porous membrane with the help of FCS [38], generating a highly hydrophilic surface. It was interesting that, despite the decreased pore sizes and porosity (Figs.…”
Section: Surface Wettability and Eumentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycols are widely used in the hydrophilic modification of membranes and in constructing antifouling interfaces because of their excellent hydration capacity and anti-protein properties [28,29]. Polyethylene glycol laurate (PEGML) is a polyethylene glycol-derived nonionic surfactant that is widely used in industries because of its low price, low toxicity, volatility, and biodegradability [30]. At the same time, it can be deposited onto the PTFE membrane surface by hydrophobic interactions and van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%